1995
DOI: 10.1203/00006450-199505000-00002
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Placental Transport of Glycine and Leucine in Human Pregnancies

Abstract: L-[I-13 C]Glycine and L-[I-13 C]leucine were infused as a bolus into 12 pregn ant patients carrying normal fetuses before fetal blood sampling at gestational ages ranging from 20 to 37 wk. Maternal venous samples were obtained every 2-3 min for 15 min after the bolus infusion . Fetal samples were obtained from the umbilical vein within 15 min of the bolus. Amino acid plasma enrichments (molar percent enrichment) were determined by gas chromatography-mass spectroscopy and their concentrations by ion exchang e c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0
3

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 17 publications
5
18
0
3
Order By: Relevance
“…Leucine has been shown to be an effective stimulus for fetal insulin in human fetal pancreas studied in vitro (18). In addition, in vivo studies applying stable isotope techniques have provided evidence to suggest that leucine taken up across the MVM is rapidly transferred to the fetus (45). Therefore, we suggest that the increased leucine transport across the MVM in the GDM/LGA group increases the leucine delivery to the fetus and contributes to the accelerated fetal growth in these patients.…”
Section: Discussionmentioning
confidence: 91%
“…Leucine has been shown to be an effective stimulus for fetal insulin in human fetal pancreas studied in vitro (18). In addition, in vivo studies applying stable isotope techniques have provided evidence to suggest that leucine taken up across the MVM is rapidly transferred to the fetus (45). Therefore, we suggest that the increased leucine transport across the MVM in the GDM/LGA group increases the leucine delivery to the fetus and contributes to the accelerated fetal growth in these patients.…”
Section: Discussionmentioning
confidence: 91%
“…During the second half of gestation, increasing placental surface area does not match the increase in fetal size, therefore increasing amino acid transporter abundance and capacity is necessary for appropriate fetal growth. In addition, in vivo human and sheep studies have shown that many amino acids transferred to the fetus are produced in the placenta through interconversion of metabolically related amino acids [111,112].…”
Section: Placental Amino Acid Transfer and Metabolismmentioning
confidence: 99%
“…This establishes the fact that in the fetal sheep, serine requirements must be met by endogenous fetal serine production. A recent study suggests that a similar situation exists in the human fetus (24). Several studies have led to the hypothesis of interorgan cycling between the the placenta and the fetus (particularly the fetal liver) for these two amino acids (2,23).…”
Section: ---------------------mentioning
confidence: 94%